Prevalence and associated factors of hypertension in selected urban and rural areas of Dhaka, Bangladesh: Findings from SHASTO baseline survey - Hasan, Mehedi; Khan, Md Showkat Ali; Sutradhar, Ipsita; Hossain, Md Mokbul; Hossaine, Moyazzam; Yoshimura, Yukie; Choudhury, Sohel Reza; Sarker, Malabika; Mridha, Malay Kanti (BMJ Journals, 2022)
This article was published in BMJ Open by BMJ Journals [© Author(s) (or their employer(s)) 2021. Re-use permitted under CC BY-NC. No commercial re-use. See rights and permissions. Published by BMJ.] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2020-038975 The Journal's website is at: https://bmjopen.bmj.com/content/11/1/e038975